Population Fertility As an Evaluation of The Success of Family Planning in Jatisari Village Pakisaji District, Malang Regency - Budijanto (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2019)
The decrease of fertility and improving public health are the main objectives to improve family welfare. The purpose of this study was to determine the fertility level of Kedampul Hamlet in Petung Sewu Village, Tumpang District, Malang Regency and to evaluate the success of family planning (KB) program of Couples of Reproductive Age (CRA) in that area. This research is a survey research with population of couples of reproductive ages in Kedampul Hamlet. The CRA sampling technique of the respondent is purposive, and interview as the main technique in data collection. The results showed that the fertility rate of CRA is higher in non-acceptor than the acceptor. The fertility of acceptor communities with non-acceptors are based on age of first marriage, span of reproduction period, wife's education, family income and infant mortality. There is a no significant difference in fertility based on the use of contraceptive. However, simultaneously the six independent variables have a significant relationship with fertility for acceptors and non-acceptors CRA. The largest contribution is given by the infant mortality variable and the smallest by the use of contraceptive.